Have I Been Here? Sense of Location in People With Alzheimer's Disease - Pai, Ming-Chyi; Jan, Shau-Shiun (Frontiers in Aging Neuroscience, 2020)
Background: When navigating in a particular space, a sense of being at a current location is of great help for the navigators in reaching their destination or getting back to the start. To accomplish this work, interwoven neural structures and neurons are called into play. This system is called the heading direction cell-place cell-grid cell circuit. Evidence from various neuroscience studies has revealed that the regions responsible for this circuit are damaged in the early stages of Alzheimer’s disease (AD). This may explain why wayfinding difficulty is one of the most frequent symptoms in persons with AD. The aim of this study was to examine the sense of location (SoL) in persons with mild AD, prodromal AD (prAD) and the cognitively unimpaired (CU). Methods: We invited people with mild AD, prAD and CU to participate in this study. The venue of the core experiment to assess SoL was a 660-meter path located on the university campus. The participants were instructed to take a walk on the path and press a device to indicate their arrival at each of the five carefully chosen targets. The linear deviation from the target site was compared among the groups. Results: A total of 20 AD, 28 prAD and 29 CU persons completed the study. Their Mini-Mental State Examination (MMSE) scores were on the average 20 (SD 3), 24 (3) and 28 (2). Groups were well differentiated regarding several measurements for cognitive ability and spatial navigation. As for the SoL, the hit rates of exact location with linear deviation of 16 meters or less were 0.05, 0.54 and 0.86 for AD, prAD and CU respectively. The hit rates are well correlated with the presence of getting lost (GL). Also, SoL differentiates well among CU, PrAD and AD in terms of average linear deviation. Conclusions: Our employing linear deviation by utilizing a grid-cell function device as an assessment for SoL showed distinct features among the three groups. This model can be used to develop more delicate devices or instruments to detect, monitor and aid spatial navigation in persons with prAD and AD.